Parasites of the southern silvery grebe podiceps occipitalis (aves, podicipedidae) in Chile Parasitas do mergulhão-de-orelha-amarela podiceps occipitalis (aves, podicipedidae) no Chile - González Acuña, Daniel (2017)
A total of 97 southern silvery grebes (Podiceps occipitalis), which died as the result of an oil spill on the coast of central Chile, were examined for ecto-and endoparasites. Two lice species including Aquanirmus rollandii (Philopteridae) and Pseudomenopon dolium (Menoponidae) were found from 6.2% (6/97) of birds. In 91.7% (89/97) of cases, grebes were infected with some kind of helminths. Three species of gastrointestinal helminths were detected: Eucoleus contortus (Nematoda), Profilicollis bullocki (Acanthocephala), and Confluaria sp. (Cestoda). In addition, Pelecitus fulicaeatrae (Nematoda) was removed from the tibiotarsal-tarsometatarsal articulation in 13.4% (13/97) of the specimens examined. To our knowledge, these are the first records of A. rollandii, E. contortus, and Confluaria sp. as parasites of P. occipitalis. In addition, these findings expand the distributional range of A. rollandii, E. contortus, P. fulicaeatrae, and Confluaria sp. to Chile.